1992
DOI: 10.1083/jcb.117.4.895
|View full text |Cite
|
Sign up to set email alerts
|

The three members of the selectin receptor family recognize a common carbohydrate epitope, the sialyl Lewis(x) oligosaccharide

Abstract: Abstract. The selectins (lectin-EGF-complement binding-cell adhesion molecules [LEC-CAMs]) are a family of mammalian receptors implicated in the initial interactions between leukocytes and vascular endothelia, leading to lymphocyte homing, platelet binding, and neutrophil extravasation. The three known selectins, L-selectin (leukocyte adhesion molecule-1 [LECAM-1]), E-selectin (endothelial-leukocyte adhesion molecule-1 [ELAM-1]), and P-selectin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
370
1
2

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(380 citation statements)
references
References 44 publications
7
370
1
2
Order By: Relevance
“…E-selectin is expressed on the endothelium within 2 h of stimulation, and it adheres to sialylated Lewis X sugars of leukocyte surface glycoproteins (29,50,58 and p2-integrins on leukocytes is facilitated after selectin interactions. Pj-integrin-ICAM-l adhesion appears to be critical for migration of leukocytes into tbe junctions between the endothelial cells and, ultimately, to the abluminal surface of the blood vessels.…”
Section: General Features Of Am Role In Allergic Inflammationmentioning
confidence: 99%
“…E-selectin is expressed on the endothelium within 2 h of stimulation, and it adheres to sialylated Lewis X sugars of leukocyte surface glycoproteins (29,50,58 and p2-integrins on leukocytes is facilitated after selectin interactions. Pj-integrin-ICAM-l adhesion appears to be critical for migration of leukocytes into tbe junctions between the endothelial cells and, ultimately, to the abluminal surface of the blood vessels.…”
Section: General Features Of Am Role In Allergic Inflammationmentioning
confidence: 99%
“…Both the observed secondary isotope effect and the inhibition by GDP-2F-Fuc are consistent with a charged, sp 2 -hybridized, transition-state structure. A convenient and efficient synthesis of GDP-[1-2 H]-Fuc and GDP-2F-Fuc and a nonradioactive, fluorescence assay for fucosyltransferase activity have been developed.The R-1,3-fucosylated oligosaccharide structures are central to numerous cell-cell interactions (Ichikawa et al, 1994) such as inflammation, tumor development, and blood clotting (Foxall et al, 1992;Parekh & Edge, 1994). Five distinct human R-1,3-fucosyltransferases have been cloned (KukowskaLatallo et al, 1990;Lowe et al, 1991;McCurley et al, 1995;Reguigne-Arnould et al, 1995;Sasaki et al, 1994; Weston et al, 1992a,b) and shown to have different acceptor sugar specificity.…”
mentioning
confidence: 99%
“…Furthermore, the application of a small force has been paradoxically reported to lengthen the lifetime of selectinligand bonds, whereas force beyond a threshold shortens the lifetime of selectin-ligand bonds 15-17 . Selectins contain an N-terminal calcium-dependent lectin domain, an epidermal growth factor (EGF)-like domain, a variable number of short consensus repeats (SCRs), and transmembrane and cytoplasmic domains 6,18-20 . Selectin ligands consist mainly of mucin-like sialoglycoproteins such as P-selectin glycoprotein ligand 1 (PSGL-1), and all three selectin molecules bind the tetrasaccharide sialyl Lewis X (sLe X ) 21,22 . The crystal structures of the lectin and EGF-like domains of human P-selectin, both bound and unbound to its high-affinity ligand PSGL-1 sulfoglycopeptide, SGP-3, have shown two distinct conformations of Pselectin.…”
mentioning
confidence: 99%